2019
DOI: 10.1039/c8pp90059k
|View full text |Cite
|
Sign up to set email alerts
|

Ozone—climate interactions and effects on solar ultraviolet radiation

Abstract: Conceptual representation of interactive effects of changes in greenhouse gases and ozone-depleting substances on climate and stratospheric ozone, which together with changes in aerosols, clouds and surface reflectivity determine UV-B radiation at Earth's surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(168 citation statements)
references
References 252 publications
(305 reference statements)
8
159
0
1
Order By: Relevance
“…We calculated daily exposures of UV-B in the upcoming decades based on the latest future-UV radiation models, which are in agreement that UV-B exposure is expected to remain unchanged in the tropics until 2050 due to the drastic reduction in the emission of ozone-depleting substances (ODS) and the associated recovery of the total column ozone (Bais et al, , 2019McKenzie et al, 2011;Watanabe et al, 2011;Meul et al, 2016). The same studies found that by 2100, UV-B exposure will likely have increased by up to 3% as a consequence of continued greenhouse gas (GHG) emissions.…”
Section: Projection Of Future Sst and Uv-b Exposurementioning
confidence: 66%
See 1 more Smart Citation
“…We calculated daily exposures of UV-B in the upcoming decades based on the latest future-UV radiation models, which are in agreement that UV-B exposure is expected to remain unchanged in the tropics until 2050 due to the drastic reduction in the emission of ozone-depleting substances (ODS) and the associated recovery of the total column ozone (Bais et al, , 2019McKenzie et al, 2011;Watanabe et al, 2011;Meul et al, 2016). The same studies found that by 2100, UV-B exposure will likely have increased by up to 3% as a consequence of continued greenhouse gas (GHG) emissions.…”
Section: Projection Of Future Sst and Uv-b Exposurementioning
confidence: 66%
“…Projected SST values were calculated based on an annual warming rate of 0.026 • C, which is the mean of the two warming rates reported for the central Red Sea by Chaidez et al (2017) and Osman et al (2018). Daily UV-B exposure in 2050 are identical to current exposure, while exposure in 2100 are 3% higher, representing the projected increase of UV-B radiation in the tropics according to the latest future-UV radiation models (Bais et al, 2019;Meul et al, 2016). The dotted black line indicates (1) the threshold of severely damaging UV-B exposure (i.e., >20 kJ m -2 d -1 ) for corals (Zhou et al, 2016) and (2) the climatological maximum monthly mean (31.1 • C) of the Jeddah region (Osman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, it is also discussed that the trends vary temporally and spatially, depending on the season and the altitude of different sub-regions of Piedmont. In the future, UV irradiance is projected to increase over Italy, mainly as a result of improved air quality and reduced attenuation by clouds over the area [41,66,174,175]. Despite the significance and the possible impacts of changes in solar UV irradiance, and the availability of UV irradiance measurements since the beginning of the 1990s, there is currently no study focused on its long-term changes over the last decades.…”
Section: State Of Measurements In Italymentioning
confidence: 99%
“…Due to the very complex interactions of solar UV radiation with atmospheric constituents and the features of the Earth's surface [65], modeling and predicting its changes is in many cases very uncertain [41,66,67]. Large uncertainties in the future projections (by climate models) of the main factors controlling the levels of the solar UV irradiance at the Earth's surface (especially clouds and aerosols) further increase the uncertainty in estimates of future UV changes due to the corresponding changes in climate and air quality [66]. The spectral characteristics of the interactions between UV radiation and aerosols are not yet completely understood, and are usually poorly described in radiative transfer models [41,67].…”
Section: Introductionmentioning
confidence: 99%
“…Over snow-and ice-covered areas, changes in UV radiation will depend on changes in albedo. The estimate of future UV radiation levels is uncertain, because of the assumptions in defining the development of these variables over time [6].…”
Section: Introductionmentioning
confidence: 99%